2021
DOI: 10.1038/s41467-021-21447-2
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomally unstable tumor cells specifically require KIF18A for proliferation

Abstract: Chromosomal instability (CIN) is a hallmark of tumor cells caused by changes in the dynamics and control of microtubules that compromise the mitotic spindle. Thus, CIN cells may respond differently than diploid cells to treatments that target mitotic spindle regulation. Here, we test this idea by inhibiting a subset of kinesin motor proteins involved in mitotic spindle control. KIF18A is required for proliferation of CIN cells derived from triple negative breast cancer or colorectal cancer tumors but is not re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 53 publications
6
67
0
Order By: Relevance
“…diploid cells 11 . Reasoning that the altered spindle dynamics in CIN tumors may confer sensitivity to inhibition of SAC proteins, Marquis et al 11 systematically knocked down mitotic kinesin proteins in cancer cell lines, measuring the effects on cellular proliferation. The loss of one particular protein, KIF18A, was associated with significantly decreased viability in CIN tumor cells but not their stable, near-diploid counterparts.…”
mentioning
confidence: 99%
“…diploid cells 11 . Reasoning that the altered spindle dynamics in CIN tumors may confer sensitivity to inhibition of SAC proteins, Marquis et al 11 systematically knocked down mitotic kinesin proteins in cancer cell lines, measuring the effects on cellular proliferation. The loss of one particular protein, KIF18A, was associated with significantly decreased viability in CIN tumor cells but not their stable, near-diploid counterparts.…”
mentioning
confidence: 99%
“…Chromosome oscillation must also be kept in a proper range, as its hyperenhancement by Kif18A depletion was reported to cause KT detachment and micronuclei formation [ 189 , 202 ]. This is of clinical relevance, because Kif18A depletion specifically compromises survival of CIN cancer cells [ 188 , 189 , 190 ]. Whether lowering CIN level by Kif18A depletion through enhancing chromosome oscillation acts synergistically with spindle disruption for cancer therapy is an interesting possibility to be examined.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, multiple types of cancer display elevated levels of Kif18A [ 185 , 186 , 187 ], which suppresses the amplitude of chromosome oscillation [ 152 ]. Recently, three papers reported that CIN or aneuploid cancer cells are vulnerable to Kif18A depletion, which causes spindle defects such as multipolar spindle formation [ 188 , 189 , 190 ]. It was suggested that increased rates of spindle MT polymerization in CIN cells confer an enhanced dependence on the role of Kif18A to limit MT growth [ 190 , 191 ].…”
Section: Chromosome Oscillation Plays a Role In Correction Of Erroneous Kt-mt Attachmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top 20 HUB genes were obtained by ranking the degree in cytoHubba. Their functional analysis and KEGG pathway enrichment analysis showed that they played an anti-NSCLC role mainly by participating in the mitosis of tumor cells and regulating cell cycle 11 . But the speci c function should to be veri ed.…”
Section: Discussionmentioning
confidence: 99%